Breast Cancer Risk Assessment at the Time of Screening Mammography: Perceptions and Clinical Management Outcomes for Women at High Risk. Issue 4 (26th January 2017) - Morman, Nichole A.; Byrne, Lindsey; Collins, Christy; Reynolds, Kelly; Bell, Jeffrey G.
Abstract: The purpose of this study was to evaluate the utility of a breast cancer risk assessment (BCRA) at the time of screening mammogram. Women whose BCRA indicated a high risk for cancer received a letter with instructions for breast health care and genetic counseling if appropriate. After 6 months this group received surveys to evaluate their risk perception and their recall of, and compliance with, recommendations. We also explored the impact of other variables such as a recommendation for genetic counseling and physician communication with the women. After the BCRA, the majority of high risk women reported no change in their perceived risk of cancer. A woman's perceived risk of cancer after a BCRA was significantly associated with her recall of recommendations for breast health care, but not with compliance. A recommendation for genetic counseling was not significantly related to women's perceived risk of cancer after the BCRA. Ten percent of women who should have obtained genetic counseling actually completed an appointment. Women who discussed their BCRA results with their physicians were more compliant with a six month breast exam with a doctor (53% vs 17%, p = 0.018). Overall, women felt that the BCRA was helpful and did not cause undue stress or anxiety. Although the cohort's compliance with recommendations was suboptimal, physicians' interactions with their patients may have a positive influence on their compliance.